Design of a Corn Thresher and Corn Cob Chopper Using the Pahl & Beitz Method - Unria, Habibah Isna; Hamdy, Muhammad Ihsan; Yola, Melfa; Nurainun, Tengku; Anwardi, Anwardi (Semesta Teknika, 2024)
The manual corn threshing process by farmers can slow down the processing and subsequent rotation of corn and affect the quality of the corn. In addition, waste from corn processing is not utilized correctly, so processing is needed. This study aims to design a corn threshing tool and corn cob shredder and to make the processing time more efficient so that the productivity and economy of farmers increase. The design method used is Pahl & Beitz, with four stages: planning and explaining tasks, designing product concepts, designing product shapes and details. The most recovered concept was produced based on the design method: concept variant 2. The corn threshing tool and corn cob shredder designed with a 240 kg/hour capacity can make the processing time more efficient. This is known from the results of testing. The tool can thresh 4 kg of corn in 1 minute, and corn cob waste is automatically chopped into powder that can be used as animal/poultry feed.